The Effect of Think Pair Share (TPS) Model Based on Flipped Learning on Students' Creative Thinking Skills - Andika Dirsa; Fryan Sopacua; Heppy Sapulete; Sukini Sukini; ilwandri Ilwandri; Aat Ruchiat Nugraha; Sofan Rizqi (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study was to determine the effect of Think Pair Share (TPS) model based on flipped learning on students' creative thinking skills. This type of research is quantitative research with a meta-analysis approach. The eligibility criteria in this study are research from national or international journals published in 2020-2024; research must be indexed by SINTA and Scopus, research must relate to the effect of the TPS model based on flipped learning on students' creative thinking skills, research obtained through the google scholar database, ScienceDirect, Wiley, ERIC and Hindawi, and research attaching complete data to analyse effect size. The data analysis technique is quantitative analysis by calculating the effect size value with the help of the OpenMEE application. The results of this study concluded that there was a positive effect of the TPS model based on flipped learning on students' creative thinking skills with a value of ES = 0.826; P < 0.001 with a high effect size category. This finding informs that the implementation of TPS model based on flipped learning has a significant effect on students compared to conventional model.